Gene expression patterns in Atlantic salmon (Salmo salar) with severe nephrocalcinosis. Issue 11 (21st July 2022) - Klykken, Christine; Boissonnot, Lauris; Reed, Anne Katrine; Whatmore, Paul; Attramadal, Kari; Olsen, Rolf Erik
Abstract: Nephrocalcinosis is a common disorder in farmed Atlantic salmon, but the consequences for the fish physiology are not well understood. We performed a transcriptome study in kidneys of Atlantic salmon ( Salmo salar ) smolts without and with severe chronic nephrocalcinosis (NC). The study revealed that numerous genes are differentially expressed in fish with NC compared with healthy salmon. The most evident changes in gene expression patterns in the NC group were a massive downregulation of metabolism and energy production, upregulation of signalling pathways important for tissue repair and function maintenance and upregulation of inflammatory responses. Overall, the extensive tissue damage and the gene regulation responses that affect salmon with severe nephrocalcinosis are highly likely to have dramatic consequences on fish survival.